The Timor-Leste Country Gender Action Plan (CGAP) 2021 - World Bank (Washington, DC, 2022)
Strengthening the role of women and promoting gender equality are key priorities for the Timor-Leste government and essential for achieving the World Bank’s twin goals of eradicating extreme poverty and sustainably boosting shared prosperity. The Timor-Leste Country Gender Action Plan (CGAP) provides a framework for addressing gender barriers and priorities through the World Bank Timor-Leste portfolio. The CGAP aims to contribute to the government of Timor-Leste’s (GOTL) development and gender equality goals by reducing gaps between men and women, and promoting human capital development and economic opportunities. It provides a framework to support the World Bank country team in ensuring that barriers to gender equality are effectively assessed, tracked, and targeted through its operations and advisory support. The CGAP is divided into seven chapters. Following the introduction and background, Chapter 4 provides an updated gender diagnostic to highlight key gender gaps in Timor-Leste across three key domains (endowments, economic opportunities, and voice and agency). Chapter 5 and 6 outline the government’s and the World Bank’s priorities and commitments to gender in Timor-Leste. Chapter 7 provides a framework for the CGAP and WBG engagement aimed at strengthening the integration of gender across the Timor-Leste country office’s operational portfolio, analytical products, policy, and advisory work. It also provides institutional and operational targets, with the overall goal of creating an accountable and enabling environment for achieving greater gender equality in outputs and outcomes.